Applying polygenic risk scoring for psychiatric disorders to a large family with bipolar disorder and major depressive disorder. (December 2018) - Jong, Simone; Diniz, Mateus; Saloma, Andiara; Gadelha, Ary; Santoro, Marcos; Ota, Vanessa; Noto, Cristiano; Curtis, Charles; Newhouse, Stephen; Patel, Hamel; Hall, Lynsey; O`Reilly, Paul; et al.
Abstract Psychiatric disorders are thought to have a complex genetic pathology consisting of interplay of common and rare variation. Traditionally, pedigrees are used to shed light on the latter only, while here we discuss the application of polygenic risk scores to also highlight patterns of common genetic risk. We analyze polygenic risk scores for psychiatric disorders in a large pedigree (n  ~ 260) in which 30% of family members suffer from major depressive disorder or bipolar disorder. Studying patterns of assortative mating and anticipation, it appears increased polygenic risk is contributed by affected individuals who married into the family, resulting in an increasing genetic risk over generations. This may explain the observation of anticipation in mood disorders, whereby onset is earlier and the severity increases over the generations of a family. Joint analyses of rare and common variation may be a powerful way to understand the familial genetics of psychiatric disorders. Simone de Jong et al. examine the balance of common and rare risk for psychiatric disorders in a large family with high incidence of Bipolar Disorder and Major Depressive Disorder. They find that increased polygenic risk over generations could be partially due to assortative mating, which may explain the observation of anticipation in mood disorders.